Hubungan Antara Kebiasaan Merokok, Riwayat Penyakit, Dan Masa Kerja Dengan Gangguan Saluran Pernapasan Pada Pekerja Di Sentra Industri Mebel Di Kecamatan Ngemplak Boyolali - Selviana, Ayu, Kusuma Estu Werdani, SKM., M.Kes (2017)
Furniture industry workers have a disproportionate risk of respiratory disorders due to exposured of wood dust. Smoking habits, history of diseases, and work periode was expected to increase the risk of respiratory diseases for workers. This researched was an analyze the relationship between smoking, disease history, and work periode with respiratory disorders for workers at the furniture industry centre in Ngemplak, Boyolali. This researched was a quantitative analytic with cross sectional approach. Population of this research was 58 respondents with male gender. Sample of this research were 58 respondents with a total sampling methode as the sampling technique. Chi Square statistic test were used as bivariate analysis. The results of the bivariate analysis showed an association between smoking habits (p = 0.010), history of disease (p = 0.017), and age (p = 0.041) with respiratory tract disorders in workers at the furniture industry centre in Ngemplak, Boyolali.